Experience of participation of a private medical enterprise in the pilot project «Modernization of Health Service in Tomsk Region» - G. N. Zaviyalova (Бюллетень сибирской медицины, 2009)
The activity of the medical enterprise Medsanchast' No. 3 within the pilot project «Modernization of Health Service in the Tomsk Region» in the form of integration in the obligatory medical insurance (OMI) system has been analyzed. Medsanchast' No. 3 has achieved significant progress in the work on the increase of its fraction if the OMI system. However, in the process of implementation of the pilot project, a critical financial situation took place due to age characteristics of new contingent and, as a consequence, payment for acute hospital aid. To solve this problem, it is necessary to revise the charge for urgent hospitalization and the order of population assignment to medical-prophylactic enterprises, thus creating equal conditions for private clinics, and to tighten control over cases of urgent hospitalization.